In situ methane enrichment with vacuum application to produce biogas with higher methane content - AKGÜL, DENİZ; ÇALLI, BARIŞ (My University, 2024)
Sludge produced in sewage treatment plants is an important source of organic matter to be used in anaerobic digestion to produce energy-rich biogas. The biogas produced in anaerobic digesters has a critical impact on achieving carbon neutrality and improving energy self-sufficiency. After effective upgrading, biogas can be converted into biomethane with an increased CH4 content, resulting in a higher volumetric energy value. Upgrading biogas to biomethane thus not only improves its energy content but also broadens its potential uses. In this study, it was aimed at enrich CH4 by removing dissolved CO2 from the digestate using a vacuum, leveraging the solubility differences of gases in liquid. In this context, two digesters (R-T and R–C) were operated for 194 days, and the effect of vacuum on in-situ methane enrichment was investigated. The vacuum was only applied to the test reactor (R-T), and the CH4 percentage was increased from 63 to 87, 80, and 75% in the vacuum exposure time intervals of 30, 10, and 5 min, respectively. Extended durations were not tested, as the rate of enrichment decreased sharply after 30 min. The maximum energy requirement of a vacuum application was estimated at 0.124 kWh/ m3 methane. Conversely, vacuum application did not cause any deterioration in biogas production, and the methane yields were similar in both reactors. Keywords Biogas upgrading, Carbon dioxide, Digestate, Biomethane, Waste activated sludge, Negative pressure
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Health Sciences; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Yaşam Bilimleri (LIFE); Mühendislik; Farmakoloji ve Toksikoloji; MÜHENDİSLİK, ÇEVRE; TOKSİKOLOJİ; Engineering, Computing & Technology (ENG); Life Sciences (LIFE); ENGINEERING; PHARMACOLOGY & TOXICOLOGY; ENGINEERING, ENVIRONMENTAL; TOXICOLOGY; Çevre Kimyası; Fizik Bilimleri; Kirlilik; Sağlık, Toksikoloji ve Mutajenez; Environmental Chemistry; Physical Sciences; Pollution; Health, Toxicology and Mutagenesis; Biogas upgrading; Biomethane; Carbon dioxide; Digestate; Negative pressure; Waste activated sludge